2022
DOI: 10.1021/acs.chemmater.2c00305
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Nitrides Are Heating Up the Field of Plasmonics

Abstract: Metal nitride nanostructures have been predicted to exhibit plasmonic responses in the UV to IR region, which can enable their potential use as low-cost, chemically, and thermally stable materials in several applications. In the case of photothermal applications, nitrides have been shown, both numerically and experimentally, to perform better than the noble metals. Additionally superior thermal stability of the metal nitride materials offers compatibility with high temperature device fabrication techniques. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 112 publications
(216 reference statements)
0
35
0
Order By: Relevance
“…1−7 A photoexcited plasmonic nanostructure can initiate a series of de-excitation pathways via radiative (scattering or emission of photons) and nonradiative processes (electron−electron, electron−phonon, or phonon−phonon interactions), resulting in unique plasmonic outcomes. 8,9 Each of these intriguing relaxation processes has earned them a special place in the areas of surface-enhanced Raman scattering (SERS), 10,11 plasmonic photocatalysis, [1][2][3][4][5][6][7]12,13 and thermoplasmonics. 14−20 Thoughtful use of nanostructured materials as well as reaction conditions is crucial to minimize the interference between the different relaxation processes, and thereby achieve the desired outcome.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1−7 A photoexcited plasmonic nanostructure can initiate a series of de-excitation pathways via radiative (scattering or emission of photons) and nonradiative processes (electron−electron, electron−phonon, or phonon−phonon interactions), resulting in unique plasmonic outcomes. 8,9 Each of these intriguing relaxation processes has earned them a special place in the areas of surface-enhanced Raman scattering (SERS), 10,11 plasmonic photocatalysis, [1][2][3][4][5][6][7]12,13 and thermoplasmonics. 14−20 Thoughtful use of nanostructured materials as well as reaction conditions is crucial to minimize the interference between the different relaxation processes, and thereby achieve the desired outcome.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Forming and breaking of high energy chemical bonds with plasmons is an emerging paradigm in materials science. A photoexcited plasmonic nanostructure can initiate a series of de-excitation pathways via radiative (scattering or emission of photons) and nonradiative processes (electron–electron, electron–phonon, or phonon–phonon interactions), resulting in unique plasmonic outcomes. , Each of these intriguing relaxation processes has earned them a special place in the areas of surface-enhanced Raman scattering (SERS), , plasmonic photocatalysis, ,, and thermoplasmonics. Thoughtful use of nanostructured materials as well as reaction conditions is crucial to minimize the interference between the different relaxation processes, and thereby achieve the desired outcome. For example, the success of plasmonic photocatalysis relies on the timely and efficient extraction of hot charge carriers from the nanostructures (in the order of a few femtoseconds). , Failing this, the entire excitation energy will be dissipated as heat to the nanoparticle lattice, and finally, to the surroundings (often termed as thermalization or the local heating process), , which triggers different photothermal processes.…”
Section: Introductionmentioning
confidence: 99%
“…18 More importantly, TMNs produce a photothermal effect under light irradiation, which would increase the temperature of the entire reaction system to elevate surface reaction kinetics. 19 Herein, two-dimensional Ni 3 N nanosheets, as a typical TMN, have been prepared and then integrated with onedimensional Cd 0.9 Zn 0.1 S (CZS) nanorods to form a twodimensional (2D)/one-dimensional (1D) Ni 3 N/CZS heterojunction by a self-assembly method. Various characterizations showed that the loading of the plasmonic Ni 3 N cocatalyst can not only induce the directional transfer of photogenerated carriers and inhibit carrier recombination but also enhance the light absorption and offer heat to enhance the reaction temperature to promote the reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies have predominantly focused on TiN which exhibits broad absorption with localized surface plasmon resonance (LSPR) maximum typically in the near-IR region. 6 As such, TiN has been explored for solar light driven processes such as water evaporation 4,5 and photocatalysis [7][8][9] and applications that require absorption in the biological transparency window such as photothermal therapy 10 and photoacoustic tomography. 11 Moving down the group, ZrN and HfN have also been explored which possess LSPR in the visible region of the electromagnetic spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic metal nitrides have recently received significant interest as reports outlining multiple synthetic methods to prepare free-standing nanoparticles (NPs), [1][2][3] demonstrating their thermal stability, 4 and high photothermal efficiency 4,5 have emerged.…”
Section: Introductionmentioning
confidence: 99%